2021
DOI: 10.47067/ramss.v4i2.156
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Problems among Patients Suffer in HIV/AIDS in Pakistan

Abstract: This study examines the treatment motivation, stigma, and disclosure in 287 HIV-infected patients in Pakistan. Four validation scales were applied to assess treatment motivation, stigma and disclosure of patients. The results showed that female patients had significantly higher levels of stigma and disclosure than male patients. Unmarried patients had significantly higher levels of stigma and disclosure than married patients. Moreover, the treatment motivation significantly positively correlated with self-disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Because of the high stigma associated with HIV/AIDS in Pakistan (Ahmed et al, 2021d;Hussain et al, 2021), and to maintain physical distance due to the COVID-19 pandemic, the NACP of Pakistan approved the study's conduct, with all interviews to be conducted by a female nurse (MJ), who works as a health counsellor in the ART centre. PLWHA were familiar with her and were willing to participate in the study.…”
Section: Interview Guide Development and Data Collection Proceduresmentioning
confidence: 99%
“…Because of the high stigma associated with HIV/AIDS in Pakistan (Ahmed et al, 2021d;Hussain et al, 2021), and to maintain physical distance due to the COVID-19 pandemic, the NACP of Pakistan approved the study's conduct, with all interviews to be conducted by a female nurse (MJ), who works as a health counsellor in the ART centre. PLWHA were familiar with her and were willing to participate in the study.…”
Section: Interview Guide Development and Data Collection Proceduresmentioning
confidence: 99%
“…These concerns were found to be higher in females and unmarried patients in comparison to other PLWH. 27 Furthermore, this life-threatening condition is traumatic for the patient and they experience intrusive thoughts about illness and death. In these scenarios, depression and PTSD emerge as the most frequently occurring phenomena requiring urgent medical and psychological care.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that only 29 percent of married women, those who had age brackets between 15 and 49 years, and all women are employed, compared to 98 percent of married men between the age bracket of 15 and 49 years (Navidi et al, 2022). Only half of the women earning cash can make independent spending decisions, according to a Karachi survey on fishermen's knowledge of HIV/AIDS (Hussain et al, 2021). Seven out of ten women reported earning less than their husbands did.…”
Section: Introduction 1acquiredmentioning
confidence: 99%